Cisplatin-induced pyroptosis is mediated via the CAPN1/CAPN2-BAK/BAX-caspase-9-caspase-3-GSDME axis in esophageal cancer. (1st July 2022) - Li, Rong-Yao; Zheng, Zhen-Yuan; Li, Zhi-Mao; Heng, Jing-Hua; Zheng, Ya-Qi; Deng, Dan-Xia; Xu, Xiu-E; Liao, Lian-Di; Lin, Wan; Xu, Hong-Yao; Huang, He-Cheng; Li, En-Min; et al.
Abstract: Esophageal cancer is the seventh most common cancer globally. Chemotherapy resistance remains a significant challenge in the treatment of esophageal cancer patients. Cisplatin can damage tumor cells by inducing pyroptosis. However, the underlying molecular mechanisms remain unclear. In this work, we aim to investigate pyroptosis-dependent molecular mechanisms underlying cisplatin sensitivity and find potential biomarkers to predict response to cisplatin-based chemotherapy for esophageal cancer patients. Pyroptosis-associated proteins were screened via proteomics for esophageal cancer ( n  = 124) and bioinformatics analysis. We observed that high calpain-1 (CAPN1) and calpain-2 (CAPN2) expression were associated with favorable clinical outcomes and prolonged survival in esophageal cancer patients. We employed immunohistochemistry to evaluate the expression of CAPN1 and CAPN2 in pretreatment tumor biopsies from 108 patients with esophageal cancer who received concurrent chemoradiotherapy (CCRT). These results suggested that esophageal cancer patients with high expression of both CAPN1 and CAPN2 are likely to experience a complete response to CCRT and have significantly better survival. Western blotting, LDH release, calpain activity and cell viability assays indicated that cisplatin could activate calpain activity, while calpain inhibition or knockout suppressed cisplatin-induced pyroptosis. Mechanistically, we uncovered a novel mechanism whereby cisplatin induced pyroptosis via activation of a CAPN1/CAPN2-BAK/BAX-caspase-9-caspase-3-GSDME signaling axis in esophageal cancer cells. Collectively, this study is the first to explore the effects of calpain on cisplatin-induced pyroptosis in esophageal cancer cells. Further, our findings also imply that the combination of CAPN1 and CAPN2 could be considered as a promising biomarker of cisplatin sensitivity and prognosis in patients with esophageal cancer, providing a possibility to guide individualized treatment. Graphical abstract: Image 1 Highlights: CAPN1 and CAPN2 as potential biomarkers of cisplatin sensitivity have good prognostic value for esophageal cancer patients. Cisplatin activates calpain activity and promotes esophageal cancer cell pyroptosis. CAPN1 and CAPN2 enhance GSDME activation and pyroptosis after exposure to cisplatin. Cisplatin can induce pyroptosis by the CAPN1/CAPN2-BAK/BAX-caspase-9-caspase-3-GSDME axis.